2019
DOI: 10.1016/j.biopsycho.2019.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent measurement of genital lubrication and blood flow during sexual arousal

Abstract: Highlights  Sexual arousal measured in response to stimuli of varied sexual activity intensity.  Genital lubrication measured using litmus test strips.  Genital blood flow assessed using laser Doppler imaging.  Greater genital responses for high-intensity sexual stimuli relative to nonsexual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 35 publications
2
15
1
1
Order By: Relevance
“…Furthermore, it is still unclear what a lower genital response means in terms of the functional implications. That is, although it is widely held that less genital blood flow results in less genital lubrication, 65 there is mixed evidence for this assertion, based on objective measures of genital lubrication, 39,66,67 and in the present study, groups did not differ on the FSFI lubrication subscale. In addition, even if lower blood flow to the genitals during an erotic film does translate to less vaginal lubrication, the realworld implications may be negligible, given the wide availability of vaginal lubricants and the fact that many women may prefer tactile sexual stimuli instead of, or in addition to, visual sexual stimuli.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Furthermore, it is still unclear what a lower genital response means in terms of the functional implications. That is, although it is widely held that less genital blood flow results in less genital lubrication, 65 there is mixed evidence for this assertion, based on objective measures of genital lubrication, 39,66,67 and in the present study, groups did not differ on the FSFI lubrication subscale. In addition, even if lower blood flow to the genitals during an erotic film does translate to less vaginal lubrication, the realworld implications may be negligible, given the wide availability of vaginal lubricants and the fact that many women may prefer tactile sexual stimuli instead of, or in addition to, visual sexual stimuli.…”
Section: Discussioncontrasting
confidence: 62%
“…65 However, recent research has found a moderate correlation between genital blood flow and lubrication (ie, r ¼ 0.41), suggesting that lower levels of genital blood flow do not directly correspond with lower levels of genital lubrication and vice versa. 39 Furthermore, other studies have reported no relationship between vaginal vasocongestion (as measured by vaginal photoplethysmography), and vaginal lubrication. 66,67 Certainly, although the absence of vaginal lubrication may be related to sexual concerns (eg, pain during penetrative sexual activity), it is unclear whether lower relative levels of genital blood flow have problematic functional outcomes.…”
Section: Lower Genital Response After Vaginal Birthmentioning
confidence: 98%
See 1 more Smart Citation
“…In this sense, vasocongestion is protective in that it primes the system for downstream aspects of the genital response. Bouchard, Dawson, Shelley, and Pukall (2019) found that more introital lubrication was produced in response to high-intensity (intercourse) versus low-intensity (kissing and caressing) male-female sexual activity, and that lubrication was associated with vulvar blood flow (assessed using laser Doppler imaging) for the high-intensity stimuli only. This supports the idea that certain types of stimuli are required to elicit lubrication, or at least a sufficient amount to be detected at the introitus by the strip.…”
Section: Assessing Lubrication Directlymentioning
confidence: 92%
“…If vaginal vasocongestion is an initial response caused by the presence of any sexual stimuli that prepares for lubrication to occur, and lubrication is a subsequent response influenced by actual likelihood of sexual activity, the correlation may not be strong (especially when only sexual stimuli are considered when calculating the correlation). Notably, lubrication was moderately associated with vulvar blood flow in one study (between-subject correlation of .41 for high-intensity sexual stimuli; Bouchard et al, 2019), which was itself moderately correlated with vaginal pulse amplitude in another study (between-subject correlation of .38 for high-intensity sexual stimuli; Bouchard et al, 2017), suggesting that the physiological processes that comprise the female genital response are distinct yet related.…”
Section: Future Directionsmentioning
confidence: 97%